A battery-less power supply using supercapacitor as energy storage powered by solar - A. Malek, Mohammad Hadin; Mustafa, Farahiyah; Mohd Asry, Anis Maisarah (Institute of Advanced Engineering and Science, 2019)
This paper presents a battery-less power supply using supercapacitor as energy storage powered by solar. In this study the supercapacitor as energy storage, as opposed to batteries, has widely researched in recent years. Supercapacitors act like other capacitors, but their advantage is having enormous power storage capabilities. Maximum charging voltage and capacitance are two variables of storage in the supercapacitor. The supercapacitor is used as energy storage to charge a low power device wirelessly and act as a power supply. The solar energy is used as a backup power supply if there is no electricity in the remote or isolated area to charge the supercapacitor. The time taken to charge the supercapacitor depend on the amount of current rating of the solar panel. The higher the current, the shorter the time taken to charges the supercapacitor. Power supply using supercapacitor can store up to 30 Vdc using a DC-DC boost converter.